Peranan Tallyman Dalam Menunjang Kelancaran Kegiatan Bongkar Muat di Pelabuhan Tanjung Emas Semarang - Juwarlan Juwarlan; Prijo Harsono (Jurnal Maritim Polimarin, 2020)
This research discusses the role of tallyman in supporting the smooth loading and unloading activities at the port of Tanjung Emas Semarang. The main problem in this study is to determine the role of tallyman in supporting the smooth running of loading and unloading activities at the port of Tanjung Emas Semarang and and how influential the role of tallyman is in supporting the smooth running of loading and unloading activities at the port of Tanjung Emas Semarang. The purpose of this study was to determine the role of the tallyman in supporting the smooth loading and unloading activities at the port of Tanjung Emas Semarang and to determine the effect of the role of the tallyman in supporting the smooth running of loading and unloading activities at the port of Tanjung Emas Semarang. This type of research is causal associative with a quantitative approach. The data collection method consists of three ways, namely: observation, questionnaires, documentation. The samples in this study were employees of 2 loading and unloading companies and a company using tallyman services operating at the port of Tanjung Emas Semarang with a total sample of 51 respondents. The instrument validation test was carried out by using correlation techniques (statistical product and service solutions and the instrument reliability test using Alpha Crombach which was calculated using SPSS version 19. The test results with SPSS 19 obtained that the regression coefficient value has a positive direction and the value of t count = 11.480 with a significance level of 0.000. By using a significance limit of 0.05, the significance value is 0.000, 0.05. Meanwhile, from the results of statistical calculations using SPSS 19, the Adjustered R2 value is 0.723.This means that 72.3% of the smooth loading and unloading activities can be affected by tallyman while the rest amounted to 27.7% influenced by other factors.